Roles of Case Studies and Case Reports in US East Asian Medicine: A Narrative-Medicine Perspective - Sarah E. Rivkin (Wolters Kluwer Health/LWW, 2023)
Recorded stories of the clinical encounter stretch back to ancient times. Throughout their history, these narratives have been called by different names, reflecting changes in format, function, and audience. This paper examines and explains the differences in two related forms of clinical writing as practiced by East Asian Medicine clinicians in the United States today-the case study and the case report. Each has its strengths and weaknesses; each is suited to different roles. The case study is ideal for education and the practice of narrative medicine, whereas the case report has played a vital role in propelling East Asian Medicine into the arena of modern scientific research.